Konsep Ijtihad Wahbah Al-Zuhaili Dan Yusuf Al-Qaradhawi Dalam Menyikapi Problematika Perkembangan Ekonomi Islam Kontemporer - Ach. Zubairi; Muhajirin (Pusat Riset dan Inovasi Nasional, 2025)
Along with the increasingly complex development of the era, of course the problems of Islamic economics are also increasingly complex. Therefore, there needs to be a continuous study of the concept of ijtihad of scholars in responding to the problems of Islamic economic development. This study analyzes the concept of ijtihad of Wahbah al-Zuhaili and Yusuf al-Qaradhawi in responding to the problems of contemporary Islamic economic development. The purpose of this study is to determine the relevance of the concept of ijtihad of Wahbah al-Zuhaili and Yusuf al-Qaradhawi in responding to the problems of contemporary Islamic economic development. This study is a descriptive qualitative study with a literature study method or what is known as (Library Research). Information is collected from books, journals, or other research findings related to the application of the theory of ijtihad of Wahbah al-Zuhaili and Yusuf al-Qaradawi to economic problems. The results of this research show that the concept of ijtihad from Wahbah al-Zuhaili and Sheikh Yusuf Qaradawi is not only relevant in academic and religious environments, but also in the business world which is increasingly complex and requires correct decisions in legal aspects.